Exploring the sources of self-efficacy by Flemish school principals in primary education. (May 2023) - Bellemans, Lore; Devos, Geert
Self-efficacy is a perceived judgment that one has the ability to execute a course of action that brings about a desired result. While a growing body of research demonstrates the importance of self-efficacy by school leaders, little is known about the different sources of principals' self-efficacy. This qualitative study investigates the relevance of Bandura's sources of self-efficacy and on potential additional sources. The analysis is based on semi-structured interviews with 23 primary school principals in Flanders (Belgium). The results reveal that mastery experiences prove to be the most powerful source of principal self-efficacy although they are mainly small successes and do not refer to extraordinary achievements or excellent results. This study also emphasizes the importance of verbal or social persuasion and gaining knowledge. Suggestions for further research, limitations and implications of this study are discussed.